Using co-design to improve the client waiting experience at an outpatient mental health clinic - Zoe Findlay; Andrea E Waddell; Maame Darkwa; Katrina Engel; Anne-Marie Voyer (BMJ Open Quality)
Prolonged wait times in healthcare are a complex issue that can negatively impact both clients and staff. Longer wait times are often caused by a number of factors such as overly complicated scheduling, inefficient use of resources, extraneous processes, and misalignment of supply and demand. Growing evidence suggests a correlation between wait times and client satisfaction. This relationship, however, is complex. Some research suggests that client satisfaction with wait times may be improved with interventions that enhance the waiting experience and not actual wait times. This project aimed to improve the average daily rating of the client waiting experience by 1 point on a 7-point Likert scale.A quality improvement study was conducted to analyse client satisfaction with wait times and enhance clients’ satisfaction while waiting. Quality improvement methods, mainly co-design sessions, were used to co-create and implement an intervention to improve clients’ experience with waiting in the clinic.The project resulted in the implementation of a whiteboard intervention in the clinic to inform clients where they are in the queue. The whiteboard also included static data summarising the average wait times from the previous month. Both aspects of the whiteboard were designed to allow patients to better approximate their wait times. Though the quantitative analysis did not reveal a 1-point improvement on a 7-point Likert scale, the feedback from staff and clients was positive. Since implementation, clinic staff and management have developed the intervention into a high-fidelity digital board that is still in use today. Furthermore, the use of the intervention has been extended locally, with additional ambulatory clinics at the hospital planning to use the set-up in their clinic waiting rooms.